Polish-Ukrainian Cooperation Concerning Cultural Heritage Protection on the Example of the City of Zhovkva (Ukraine) - Volodymyr Herych (Barometr Regionalny)
Signed in 1992 The Contract between the Government of Ukraine and the Government of the Republic of Poland on Cultural and Scientific Cooperation provides opportunities for cooperation in the field of cultural heritage protection. In the paper are shown examples of such cooperation between city of Zhovkva (Ukraine) and Polish cultural institutions.